2018
DOI: 10.1371/journal.pmed.1002565
|View full text |Cite
|
Sign up to set email alerts
|

Access to antiretroviral therapy in HIV-infected children aged 0–19 years in the International Epidemiology Databases to Evaluate AIDS (IeDEA) Global Cohort Consortium, 2004–2015: A prospective cohort study

Abstract: IntroductionAccess to antiretroviral therapy (ART) is a global priority. However, the attrition across the continuum of care for HIV-infected children between their HIV diagnosis and ART initiation is not well known. We analyzed the time from enrollment into HIV care to ART initiation in HIV-infected children within the International Epidemiology Databases to Evaluate AIDS (IeDEA) Global Cohort Consortium.Methods and findingsWe included 135,479 HIV-1-infected children, aged 0–19 years and ART-naïve at enrollme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 37 publications
0
34
0
3
Order By: Relevance
“…Even on ART, chronic immunodeficiency could alter growth . We observed a trend of poorer growth evolution among males attending rural clinics, which suggests higher vulnerability of APH living in rural settings that could be related to poverty and food access as well as the general challenges of ART adherence and retention in HIV care observed during adolescence .…”
Section: Discussionmentioning
confidence: 71%
“…Even on ART, chronic immunodeficiency could alter growth . We observed a trend of poorer growth evolution among males attending rural clinics, which suggests higher vulnerability of APH living in rural settings that could be related to poverty and food access as well as the general challenges of ART adherence and retention in HIV care observed during adolescence .…”
Section: Discussionmentioning
confidence: 71%
“…Men, adolescents, those with lower education levels, and the poorest individuals are less likely to be aware of their status, resulting in late initiation of treatment, as well as lower and later attainment of viral suppression . Infants less than 18 months of age are also at risk of delays in care enrollment and treatment initiation because of challenges in early infant diagnosis testing, especially in resource‐limited settings . Estimating the “first 90” for key populations (e.g.…”
Section: Resultsmentioning
confidence: 99%
“… Context: Global data suggest that the timeliness of ART initiation, as measured by the level of immunodeficiency at the start of ART, is highly suboptimal in relation to WHO guidelines, particularly in SSA, where a recent analysis of data from 767,000 patients in 21 countries showed that median CD4 counts at ART initiation remained below 300 cells/mm 3 in 2015 . Infants, adolescents, and men, in particular, are more likely to initiate treatment late and to not be retained in care . Research approaches : Important factors for further study include quality of care; policy and administrative requirements; costs of services, including user fees; HIV‐related stigma; integrated screening and treatment of other health conditions (i.e. non‐communicable diseases); and community‐ and home‐based services (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the IeDEA Global Cohort, which is comprised of cohorts with different infrastructures, reported that overall N a t r i s k 0 1 2 3 4 5 6 7 8 9 1 0 1 1 1 2 2008-2013 21825 15648 13447 12406 11716 11290 10986 10716 10454 10244 10059 9913 9763 2014-2018 29782 14174 10160 8679 7843 7284 6853 6468 6118 5829 5594 LTFU (defined as clinic absence of >6 months) before starting ART was 20.4%, but only 2.3% in the Asia-Pacific region [35]. The majority of Asian cohorts in the IeDEA study were from research centres that specifically cater for YLHIV.…”
Section: Discussionmentioning
confidence: 99%